2021
DOI: 10.1182/blood-2021-149204
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 in Hematopoietic Stem-Cell Transplant Recipients: A Single Institution Observational Study

Abstract: Intro: Hematopoietic stem-cell transplant (HSCT) recipients are considered to be at high risk for poor outcomes following COVID-19 infection given their co-morbidities and immunosuppression. Sharma et al published the CIBMTR observational report data that showed that recipients of allogeneic HSCT who contract COVID-19 have poor overall survival with a 30-day mortality of 32%. That being said, there have been relatively few studies that look into the effect of COVID-19 on HSCT recipients in the setting of in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Selected studies reported retrospective observational data from single‐centre experiences [4– 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], multicentre experiences [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] or registry data [ 7 , 8 , 42 , 43 , 44 , 45 ]. Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Selected studies reported retrospective observational data from single‐centre experiences [4– 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], multicentre experiences [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] or registry data [ 7 , 8 , 42 , 43 , 44 , 45 ]. Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 , 25 , 36 ] were from North America (238 patients), seven studies [ 5 , 16 , 21 , 26 , 30 , 32 , 42 ] were from the Middle East (185 patients), two studies [ 28 , 40 ] were from South America (41 patients), one study [ 27 ] was from Asia (28 patients) and two studies [ 7 , 43 ] included patients from multiple regions (496 patients). Seventeen studies [ 7 , 8 , 16 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 35 , 38 , 39 , 40 , 41 , 45 ] included both adult and paediatric transplant recipients, 13 studies […”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations